Persepsi dan Identifikasi Diri Etnis Minoritas Sebagai Warga Negara, studi kasus :Cina Benteng Tangerang - , Indah Juwita Sari, Samsu Rizal Panggabean, MS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cina Benteng have already known as community group of Tionghoa descendant who spread almost all over Banten Province, especially in Tangerang City. But, majority of Cina Benteng have lived along Cisadane river, precisely in Lebak Wangi Village, Mekarsari Subdistrict, Neglasari District. Cina Benteng community have assimilated with the local one. They have lived together peacefully. Rarely has conflict happened. But, there is still one main problem out of many faced by this group. It is the difficulty of obtaining identity as Indonesia Citizen (WNI). Though, more than four of their generations have lived in Indonesia. High commitment towards the citizens is absolutely required to realize a good government. One of these is giving citizen rights warrant and legal protection. Obtaining such rights needs recognition from the government mentioning that a person or social group is legally part of citizens. So, it needs a various documents to legalize their status as legitimate citizens, such as Identity Cards or ID Cards (Kartu Tanda Penduduk/KTP), Certificate of Birth, and Family Identification Card (Kartu Keluarga/KK). The difficulty of citizenship-relatedaccess causes someone or social groupâs legal status becomes unclear. This happened because their rights are not guaranteed. This research aims to know why Cina Benteng community is difficult to gain citizenship-related-access based on their perception, whether they perceive themselves as Indonesian citizen. Its important to know because their selfperception determines the relationship between in-group and out-group, not only with the local community, but also with other groups surrounding them. Besides, self-perception greatly affects their rights, obligations, and how they perceive themselves as citizens. This research uses a qualitative approach, that is bringing facts up using descriptive-narrative method. It is called case study. Case study is an intensive description and analysis of the individual by searching data from various sources, including observation and interview. This research concludes that respondents prefer to perceive themselves as Indonesian citizens who is Chinese descendant rather than as foreigner (Peopleâs Republic of China/Republik Rakyat Cina, for example). They perceive identity as a positive one, namely as an Indonesian citizen. They try to establish a positive self-concept so that they easily obtain equal right and obligation, particularly as a legally recognized citizen. They hope the local community accept them as well. They also try to keep themselves equalized and recognized as other ethnic groups in Indonesia, such as Javanese, Batak, Bugis, and so forth. So, it can be concluded that the difficulties on obtaining an identity card is not caused by minorityâs exclusivism, but rather by other factors, such as prejudice, stereotyping, economic condition, historcal aspects, and governmental policies.